Evaluation of reparative dentin formation of ProRoot MTA, Biodentine and BioAggregate using micro-CT and immunohistochemistry - Jia Kim; Young-Sang Song; Sun-Hun Kim; Jeong-Tae Koh; Kyung-San Min; Bin-Na Lee; Won-Mann Oh; Hoon-Sang Chang; In-Nam Hwang; Yun-Chan Hwang (Korean Academy of Conservative Dentistry, 2016)
Objectives The purpose of this study was to assess the ability of two new calcium silicate-based pulp-capping materials (Biodentine and BioAggregate) to induce healing in a rat pulp injury model and to compare them with mineral trioxide aggregate (MTA). Materials and Methods Eighteen rats were anesthetized, cavities were prepared and the pulp was capped with either of ProRoot MTA, Biodentine, or BioAggregate. The specimens were scanned using a high-resolution micro-computed tomography (micro-CT) system and were prepared and evaluated histologically and immunohistochemically using dentin sialoprotein (DSP). Results On micro-CT analysis, the ProRoot MTA and Biodentine groups showed significantly thicker hard tissue formation (p < 0.05). On H&E staining, ProRoot MTA showed complete dentin bridge formation with normal pulpal histology. In the Biodentine and BioAggregate groups, a thick, homogeneous hard tissue barrier was observed. The ProRoot MTA specimens showed strong immunopositive reaction for DSP. Conclusions Our results suggest that calcium silicate-based pulp-capping materials induce favorable effects on reparative processes during vital pulp therapy and that both Biodentine and BioAggregate could be considered as alternatives to ProRoot MTA.